Violence and maltreatment in intimate relationships - Miller-Perrin, Cindy L. (SAGE, 2018)
History and definitions of intimate violence and maltreatment -- Methods and perspectives in vmir -- Child physical abuse -- Child sexual abuse -- Child neglect -- Child psychological maltreatment -- Abuse in adolescent and emerging adult relationships : peer sexual harassment, sexual -- Assault, dating violence and stalking -- Intimate partner abuse in adult relationships : focusing on victims -- Intimate partner abuse in adult relationships : focusing on perpetrators -- Intimate abuse of people with disabilities and the elderly -- Societal responses to vmir: some concluding thoughts -- Glossary -- References -- Index